A concept of reactive compatibilizer‐tracer for studying reactive polymer blending processes. Issue 2 (28th October 2015) - Ji, Wei‐Yun; Feng, Lian‐Fang; Zhang, Cai‐Liang; Hoppe, Sandrine; Hu, Guo‐Hua; Dumas, Dominique
Significance: A concept called reactive compatibilizer‐tracer is proposed. The latter bears reactive groups capable of reacting with its counterpart on forming a copolymer for in situ compatibilization, and fluorescent labels allowing determining very small amounts of the in situ formed compatibilizer and formation of micelles when it occurs. Owing to this concept, it is shown that a reactive compatibilizer may be very efficient at the beginning of a reactive blending process and may suddenly become completely inefficient, resulting in an abrupt and drastic increase in size of the dispersed phase domains. © 2015 American Institute of Chemical Engineers AIChE J, 62: 359–366, 2016